Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1080/15374416.2016.1183496
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Associations Between Teacher–Child Relationship Quality and Chinese American Immigrant Children’s Behavior Problems

Abstract: The goal of the study was to test the bidirectional associations between teacher-child relationship quality and behavior problems in an elementary school age sample of Chinese American immigrant children. A socioeconomically diverse sample (N = 258) of first- and second-generation Chinese American children (M ages = 7.4 and 9.2 years at Wave 1 and Wave 2, respectively; 48% girls) was recruited from schools and communities and followed for 1 to 2 years. Two waves of data on dimensions of teacher-child relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
19
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 48 publications
6
19
2
Order By: Relevance
“…A recent study by De Laet et al (2016) reported that adolescents who display more rule-breaking behavior experienced increased dissatisfaction with their teachers, which, in turn, further increased their adjustment problems. Ly and Zhou (2016) found that teacher-rated conflict positively predicted parent-rated externalizing problems in a sample of Chinese American immigrant children.…”
Section: Teacher-student Relationships and Externalizing Problemsmentioning
confidence: 92%
See 3 more Smart Citations
“…A recent study by De Laet et al (2016) reported that adolescents who display more rule-breaking behavior experienced increased dissatisfaction with their teachers, which, in turn, further increased their adjustment problems. Ly and Zhou (2016) found that teacher-rated conflict positively predicted parent-rated externalizing problems in a sample of Chinese American immigrant children.…”
Section: Teacher-student Relationships and Externalizing Problemsmentioning
confidence: 92%
“…Roorda et al (2014) found that teacherperceived conflict had reciprocal associations with preschool boys' internalizing problems at an early phase of the school year but not during the second half of the school year. A recent study by Ly and Zhou (2016) showed among a sample of Chinese American immigrant elementary school children that those with higher levels of teacher-rated internalizing problems scored lower on teacher-rated conflict later on, whereas Zhang and Sun (2011) demonstrated a significant path from internalizing behavior to teacher-perceived conflict in Chinese preschoolers. Ly and Zhou (2016) found that the quality of the teacher-student relationship did not predict children's internalizing problems over time.…”
Section: Teacher-student Relationships and Internalizing Problemsmentioning
confidence: 97%
See 2 more Smart Citations
“…Moreover, several studies have found that different raters might account for the lack of coherence in research on the link between affective TSRs and students' EBPs. For example, some previous studies have relied on EBPs rated by students, which were only weakly related to positive indicators of affective TSRs (Troop-Gordon and Kopp, 2011; Li et al, 2012) while other studies found that student EBPs rated by teachers were moderately related to both positive indicators of affective TSRs (Colwell and Lindsey, 2003; Shin and Kim, 2008) and negative indicators of affective TSRs (White and Renk, 2012; Ly, 2013; Skalická et al, 2015). In contrast, other researchers found that student EBPs rated by teachers were strongly related to negative indicators of affective TSRs (Palermo et al, 2007; Fowler et al, 2008; Stipek and Miles, 2008).…”
Section: Introductionmentioning
confidence: 99%